2019
DOI: 10.5194/tc-2019-248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermokarst lake development in syngenetic ice-wedge polygon terrain in the Eastern Canadian Arctic (Bylot Island, Nunavut)

Abstract: Abstract. Thermokarst lakes are widespread and diverse across permafrost regions and they are considered significant contributors to global greenhouse gas emissions. Paleoenvironmental reconstructions documenting the inception and development of these ecologically important water bodies are generally limited to Pleistocene-age permafrost deposits (Yedoma) of Siberia, Alaska, and the western Canadian Arctic. Here we present the gradual transition from syngenetic ice-wedge polygon terrains to a thermokarst lake … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…depth = 12.2 m and 11.7 respectively), but lake K is smaller than lake L. We also sampled lake G (max. depth = 4.1 m) as lake bottom imagery revealed submerged ice-wedge polygons (~1 m depth) and degraded ice-wedge troughs in shallower lake G, which confirmed that this lake (G) is evolving through the melting of permafrost intrasedimental ice and ice wedges as revealed by subsiding and eroding shores (see video supplement in Bouchard et al, 2020). Two sediment cores of 109 cm and 114 cm were collected in spring 2015 from lakes G and K, respectively.…”
Section: Lake Sediments and Vertical Structuresupporting
confidence: 53%
See 4 more Smart Citations
“…depth = 12.2 m and 11.7 respectively), but lake K is smaller than lake L. We also sampled lake G (max. depth = 4.1 m) as lake bottom imagery revealed submerged ice-wedge polygons (~1 m depth) and degraded ice-wedge troughs in shallower lake G, which confirmed that this lake (G) is evolving through the melting of permafrost intrasedimental ice and ice wedges as revealed by subsiding and eroding shores (see video supplement in Bouchard et al, 2020). Two sediment cores of 109 cm and 114 cm were collected in spring 2015 from lakes G and K, respectively.…”
Section: Lake Sediments and Vertical Structuresupporting
confidence: 53%
“…2). At the lake scale, these shallow lakes have relatively flat and homogeneous lake beds with a deeper central basin surrounded by shallower nearshore zones (< 2 m deep), where submerged polygons are clearly visible (see the video supplement in Bouchard et al, 2020). These lakes have maximum depths ranging between 1 and 4 m, with mean depth reaching 1.4 ± 0.7 m across their platform (Fig.…”
Section: Morphology Of Lakes In the Qarlikturvik Valleymentioning
confidence: 95%
See 3 more Smart Citations